2014
DOI: 10.2298/vsp1404346d
|View full text |Cite
|
Sign up to set email alerts
|

When do the symptoms of autonomic nervous system malfunction appear in patients with Parkinson’s disease?

Abstract: Our results confirm a high prevalence of autonomic nervous system disturbances among PD patients from the near onset of disease, with a predominant sympathetic nervous system involvement. The patients who developed complete autonomic neuropathy (both sympathetic and parasympathetic) were individuals with considerable level of functional failure, more severe clinical presentation and the existing anxiety and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…The role of central noradrenergic dysregulation may play a role in both dysautonomia and anxiety [ 55 ]. Additionally, autonomic failure may create a pathophysiological predisposition towards the somatic symptoms of anxiety or a stronger physical response to anxiety in PD, as reported in previous research [ 56 ]. Subjects with higher RBD-HK scores was a risk factor for anxiety in PD in the study, which is in line with previous studies [ 35 , 57 ].…”
Section: Discussionmentioning
confidence: 82%
“…The role of central noradrenergic dysregulation may play a role in both dysautonomia and anxiety [ 55 ]. Additionally, autonomic failure may create a pathophysiological predisposition towards the somatic symptoms of anxiety or a stronger physical response to anxiety in PD, as reported in previous research [ 56 ]. Subjects with higher RBD-HK scores was a risk factor for anxiety in PD in the study, which is in line with previous studies [ 35 , 57 ].…”
Section: Discussionmentioning
confidence: 82%
“…Although the majority of the studies assessing cardiovascular reflexes such as the Ewing’s battery of autonomic tests, showed that parasympathetic dysfunction may be present early in the disease course, 22–24,27–29,32,33 some studies have shown that DNPD manifested only sympathetic dysfunction, either assessing cardiovascular reflexes or on the basis of cardiac radioiodinated metaiodobenzylguanidine uptake. 34 …”
Section: Resultsmentioning
confidence: 99%
“…È õîòÿ â ëèòåðàòóðå äîñòàòî÷íî óñòîé-÷èâûì ñ÷èòàåòñÿ îïðåäåëåíèå ÁÏ êàê íåéðîäåãåíåðàòèâíîãî çàáîëåâàíèÿ öåíòðàëüíîé íåðâíîé ñèñòåìû, äîñòàòî÷íî èíòåðåñíî ðàññìîòðåòü âîçìîaeíîñòü òîãî, ÷òî ïðîöåññ íà ñàìîì äåëå íà÷èíàåòñÿ â ïåðèôåðè÷åñêîé íåðâíîé ñèñòåìå. Òàê, òåëüöà è íåéðèòû Ëåâè íàéäåíû â çâåçä÷àòûõ ãàíãëèÿõ è ñåðäå÷íîì ñèìïàòè÷åñêîì ñïëåòåíèè, ïó÷êå Àóýðáàõà è ìîçãîâîì âåùåñòâå íàäïî÷å÷íèêîâ â îòñóòñòâèè ïàòîëîãèè öåíòðàëüíîé íåðâíîé ñèñòåìû [31,32]. Íåäàâíî àãðåãàòû α-ñèíóêëåèíà áûëè îáíàðóaeåíû òàêaeå â âåãåòàòèâíûõ ñïëåòåíèÿõ áðþøíîé ïîëîñòè è ïóçûðüêàõ ïðîñòàòû ïðè ïðîâåäåíèè õèðóðãè÷åñêèõ îïåðàöèé ó çäîðîâûõ ëèö áåç íåâðîëîãè÷åñêîé ïàòîëîãèè (ó îäíîãî èç êîòîðûõ áûëè âûÿâëåíû ðàññòðîéñòâà ïîâåäåíèÿ â REM-ôàçå ñíà) [4,33].…”
Section: классификации немоторных проявлений болезни паркинсонаunclassified